Self-Care Management dalam Intervensi Keperawatan Pada Kelelahan Postpartum: Tinjauan Literatu - Azlina, Fitri Ayatul (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Fatigue is a common condition that is vulnerable and persistent in postpartum mothers. The incidence ofpostpartum mothers experiencing fatigue in Indonesia is quite high. Postpartum fatigue can cause a variety ofunpleasant symptoms and affect physical and psychological health. This can interfere with the role of themother in caring for herself and baby care and can be a predictor of depression. This literature review aims toidentify Self-Care Management strategies and nursing interventions in mothers with postpartum fatigue so thatthey can be used as a reference for nurses in carrying out nursing care. The method used in this review isliterature review based on appropriate keywords. Self-Care Management and nursing interventions carried outby nurses can be used as an effort to maintain optimal postpartum mother health and newborn care.